Influence of Segmented Linings on the Micro-Pressure Wave of Tunnels - Tao Li; Mingyu Shao; Weibin Ma; Yanbin Liang; Yufei Fang (Advances in Civil Engineering)
When the tunnel has damages such as deformation and cracking, the lining structure should be set to reinforce the tunnel. In this study, a three-dimensional numerical method is performed to study the aerodynamic effects caused by the train passing through a tunnel with segmented linings at 350 km/h. The influence of the numbers, thickness, location, and types of the segmented lining structure on MPW is analyzed. The results show that the segmented linings located at the middle of the tunnel have a better mitigation effect on MPW than that of the normal linings, which increases with the segment number and the thickness of the linings. When the damage occurs near the entrance of the tunnel, a segmented lining structure with a constricted section slightly away from the tunnel entrance can be used to reduce its adverse effect on MPW.